Pelaksanaan Supervisi Akademik Berbasis Lesson Study untuk Meningkatkan Kinerja Guru di SMPN 1 Baitussalam: Implementation of Lesson Study-Based Academic Supervision to Improve Teacher Performance at SMPN 1 Baitussalam - Roslina Roslina; Rita Novita; Musdiani Musdiani (ITScience (Information Technology and Science), 2026)
Low teacher performance in preparing instructional materials and conducting innovative lessons is the primary issue at SMP Negeri 1 Baitussalam, Aceh Besar Regency; the average pre-cycle performance score was only 57.69 (classified as